Morpho-physiological and biochemical changes during seed development in cucumber (Cucumis sativus) - GUPTA, NAKUL; JAIN, S K; TOMAR, B S; ANAND, ANJALI; SINGH, JOGENDRA; SINGH, A K (The Indian Journal of Agricultural Sciences, 2021)
Morpho-physiological and biochemical changes in developing cucumber (Cucumis sativus L) seeds were monitored under both open field (E1) and protected environments (E2) during 2019 at ICAR-IARI, New Delhi. Fruits developed from hand pollinated flowers, in Pusa Barkha and Pusa Uday varieties were harvested at five-day intervals. The environment influenced both days to maturity and development of fruit and/or seed. Irrespective of varieties, seasons and environments, seed moisture decreased (over three folds); seed fresh and dry weights increased (one & half and three folds, respectively). Electrical conductance (EC), total soluble sugars (TSS) and total soluble proteins (TSP), from seed leachates, followed a bell-shape pattern. The reserve accumulation (TSS, starch, TSP and oil) registered an increase both in seed fresh and dry weights; the seed filling continued up to maturity. The ROS activity (H2O2& O2-) initially increased then decreased significantly up to maturity. A significant decrease in antioxidant enzymes indicated seed desiccation resistance. Seeds attained maximum germination (70.0 &73.2%), seed vigour-I (1114.3 &1323.1), seed vigour-II (8.61 & 9.55) during 40 DFP&50 DFP; and seed dry weights (19.9 & 20.15 mg/seed) under E1&E2, respectively.